Design and Measurement of a Minuscule-Sized Implantable Antenna for Brain–Machine Interfaces - Naeem Abbas; Sana Ullah; Zubair Bashir; Abdul Basir; Hyoungsuk Yoo (IEEE Access, 2023)
The study proposes a small dual-band implantable antenna for brain-machine interface (BMI) working over industrial, scientific, and medical (915 MHz, 2.45 GHz) bands. The antenna’s flexibility and small size allow for easy integration into implantable devices, while its dual-band resonance enables power-efficient operation. Through parametric analysis and optimization, the antenna achieves miniaturization without compromising performance. Slitted ground and patch and shorting pins techniques are used to achieve dual-band operation with miniaturized sizes of the antenna and BMI device of 9.8 mm3 and 420 mm3, respectively. For a practical scenario, a seven-layer brain model with different layers and a realistic head model were used to analyze the performance of the antenna in heterogeneous environments. The calculated maximum specific absorption rate (SAR) values satisfied the IEEE safety standards C95.1-1999 and C95.1-2005 for implantable medical devices if the maximum radiated powers are under 10.1 and 8.1 mW at 915 and 2450 MHz, respectively. To verify the simulated results, the fabricated prototype underwent testing with minced pork meat, yielding impressive impedance bandwidths of 165 MHz and 625 MHz. The measurements revealed significant gains of −28.3 dBi and −18.5 dBi at frequencies of 915 MHz and 2.4 GHz, respectively. These findings validate the accuracy of the simulations without any deviations. Moreover, the link budget analysis results suggested that the antenna system can transmit a signal of up to 10 m at a data rate of 100 kbps.